Current Cross Border e-Commerce Companies Developmental Problems AND Countermeasures - Tseng, TzuShan (Archives of Business Research, 2020)
The development of cross border e-commerce industry is one of important global trends. From eMarketer (2019), the global sales of e-commerce in 2018 was 2.5 trillion US dollars and will reach 7.5 trillion US dollars in 2020. In this number - 7.5 trillion US dollars, the cross border e-commerce consumers will occupy 44.6% of e-commerce’s. Due to the quick development, companies will encounter problems by the way. The research purposes of this study was to discuss problems found through Osterwalder and Pigneur’s business model canvas analysis and provide suggestions. In this sense, During the time of one-year industry-academic cooperation program with Company A, the exploratory case study is relying on several sources of data collections through interviews, case analysis, site-visiting observations and secondary data collection (internal and external data) to analyze Company’s A cross order e-commerce business model and Taiwan’s cross border e-commerce ecosystem. The research subject (Company A) who locate in the vehicles components industry was a Taiwanese SEM and would like to transform into a cross border e-commerce company. The study aimed to explore the cross border e-commerce business model to answer the research question of What is Company A’s recent business model canvas ? If Company A would like to transform into cross border e-commerce, what are the problems? What is Taiwan cross border e-commerce ecosystem which Company A is located ? The research results and suggestions of this cross border e-commerce company are the following. Firstly, the problem is business opportunities are difficult to catch recently and the amount of each order earned is becoming smaller. The suggestion for this problem is to suggest adapting multiple cross border e-commerce portals operations on budgets and “Software Key activities” for decision making. The second problem is the cost of cross border e-commerce logistic is high. The suggest for this problem is to use Big Data Analysis and artificial intelligence (AI) technology to calculate exact oversea inventories. The third problem is lack of trust. The suggest for this problem is localization strategy, to systematically recruit and train the talents who are familiar with the culture, products and markets. And also The study also has some practical implications for cross-border e-commerce companies.